2010
DOI: 10.1002/chem.200902004
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich Compounds of Transition Metals with Cyclopolyenes and Isolobal Boron Analogues

Abstract: A series of sandwich compounds of transition metals (M=Ni, Fe, Cr) with cyclic hydrocarbon (M(CH)(n)) and borane (M(BH(2))(n)), ligands (including mixed hydrocarbon/borane sandwiches) has been studied using density functional theory (B3LYP/6-311+G(df,p)). Multicenter bonding between the central metal atom and basal cycloborane rings provides stabilization to planar cycloborane species. Large negative NICS values allude to aromatic character in the cycloboranes similar to the analogous cyclic hydrocarbons. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…The ferrocene analogues [(η 5 -E 5 ) 2 M] (E = P, N, As, Sb, and Bi) have found important applications in both fundamental research and materials science. 1,[43][44][45][46][47][48][49] Besides, planar aromatic [Al 4 ] 2− , [50][51][52][53][54] [N 5 ] − , 49 [(P 5 ) 2 Ti] 2− , 55 borane, 56,57 CO, 58 PH 3 , 58 and boron clusters [59][60][61][62][63] can also be utilized as ligands to coordinate transition metals and form similar…”
Section: Introductionmentioning
confidence: 99%
“…The ferrocene analogues [(η 5 -E 5 ) 2 M] (E = P, N, As, Sb, and Bi) have found important applications in both fundamental research and materials science. 1,[43][44][45][46][47][48][49] Besides, planar aromatic [Al 4 ] 2− , [50][51][52][53][54] [N 5 ] − , 49 [(P 5 ) 2 Ti] 2− , 55 borane, 56,57 CO, 58 PH 3 , 58 and boron clusters [59][60][61][62][63] can also be utilized as ligands to coordinate transition metals and form similar…”
Section: Introductionmentioning
confidence: 99%
“…There are also many borane derivatives, such as metallaborane, macropolyhedral borane, and carborane. The metallaborane can be obtained by replacing the B atom of a simple borane with transitional metal atom, and some metallaboranes satisfy the 18‐electron rule . The condensation of two or more simple borane units by sharing one to four vertexes forms the macropolyhedral borane .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, for Cr(C 6 H 6 ) 2 , a benzene molecule (C 6 H 6 ) contributes six π electrons as π -bonding ligand and the Cr (3d 4 4s 2 ) atom contributes six electrons, which also meets the 18-electron principle. With more studies on sandwich compounds, the ligands are various and include not only hydrocarbons, e.g., borane, 28,29 CO, 30 PH 3 ,30 boron clusters, [31][32][33][34][35] etc. The spectroscopic and theoretical studies have shown that boron clusters have planar geometries and exhibit aromatic and antiaromatic electronic properties analogous to hydrocarbons, 36 so they are predicted to be promising molecules for coordination chemistry as potential new ligands and for materials science as new building blocks.…”
Section: Introductionmentioning
confidence: 99%